Now Trending: Social Media and Crowdfunding For Disaster-Stricken Indian Sundarbans - Basu, Anindya (Indonesian Journal of Geography, 2025)
A paradigm shift in disaster risk reduction and management is evident, with social media and crowdfunding playing an important role, even in disaster-prone developing countries like India, with a pronounced digital divide. With the advent of social media platforms coupled with the frequent landfalls of cyclones in the Indian Sundarbans, a climate hotspot has become a classic example of this trio - social media, crowdfunding, and disaster tourism. The main objectives are to bring out the essence of changing the relief donation scenario from traditional donation to modern digital crowdfunding, to assess how far technology and social media, more specifically, have been able to help the eager contributors to take part in the cause of disaster management through hypothesis testing, regression analysis, SWOT analysis, focus group discussions, and perception studies. The empirical research (carried out between 2022-23) based on a semi-structured questionnaire survey involved the stakeholders –donors and beneficiaries. The study notes the nature of social media platform usage, identifies the main driving forces behind opting for specific donation drives, and delves into the underlying reasons for undertaking disaster tourism trips. The study shows that increased use of social media has led to greater acceptance of online crowdfunding initiatives, especially among the younger and educated.